2011
DOI: 10.1073/pnas.1109493108
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A and Tenascin-C produced by S100A4 + stromal cells are important for metastatic colonization

Abstract: Increased numbers of S100A4 + cells are associated with poor prognosis in patients who have cancer. Although the metastatic capabilities of S100A4 + cancer cells have been examined, the functional role of S100A4 + stromal cells in metastasis is largely unknown. To study the contribution of S100A4 + stromal cells in metastasis, we used transgenic mice that express viral thymidine kinase under control of the S100A4 promoter to specifically ablate S100A4 + stromal cells. Depletion of S100A4 + stromal cells signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
272
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(279 citation statements)
references
References 32 publications
5
272
0
2
Order By: Relevance
“…Previous studies have identified cancer-associated fibroblasts as a major source of Tnc in tumors (39), but whether stroma-derived Tnc has a role in tumor progression in this model is unclear. Although the precise mechanism of action remains to be elucidated, we have shown that Tnc is a target of the transcription factor Nkx2-1, which has been shown to suppress lung cancer progression and metastasis through the suppression of embryonic genes (19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified cancer-associated fibroblasts as a major source of Tnc in tumors (39), but whether stroma-derived Tnc has a role in tumor progression in this model is unclear. Although the precise mechanism of action remains to be elucidated, we have shown that Tnc is a target of the transcription factor Nkx2-1, which has been shown to suppress lung cancer progression and metastasis through the suppression of embryonic genes (19).…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, it has been demonstrated that the ablation of S100A4 in stromal cells significantly reduced metastatic colonization by regulating matrix protein tenascin-C and growth factor vascular endothelial growth factor (VEGF)-A. 32 In previous studies, we found an additional mechanism of action that S100A4 + fibroblasts promote skin carcinogenesis by maintaining MCP-1-mediated macrophage infiltration and chronic inflammation. 20 In addition, we identified a critical role of S100A4 in promoting liver fibrosis through hepatic stellate cell activation, 21 and macrophage-derived S100A4 promotes liver carcinogenesis by promoting CD8 + T-cell survival (unpublished).…”
Section: Introductionmentioning
confidence: 95%
“…This hypothesis is supported by data showing that VEGFA is instrumental in tenascin-C enhanced lung metastasis of 4T1 cells. 105 Yet a potential link to radiotherapy still has to be investigated.…”
Section: Induction Of Tenascin-c Upon Radiotherapymentioning
confidence: 99%